DOSES DE SILÍCIO EM MUDAS D E SERINGUEIRA SOB DIFERENTES AMBIENTES - PEREIRA, Talita Cristina Campos; AGUIAR, Franciele Kelle Oliveira Moura; PAULINO, Leonardo Albino; SALLES, Josiane Souza; COSTA, Edilson; SCALOPPI JÚNIOR, Erivaldo José (ANAIS DO ENIC, 2018)
-